The composition of a bioprocessed shiitake (Lentinus edodes) mushroom mycelia and rice bran formulation and its antimicrobial effects against Salmonella enterica subsp. enterica serovar Typhimurium strain SL1344 in macrophage cells and in mice - Kim, Sung Phil (BMC Complement Altern Med, 2018)
BACKGROUND: Human infection by pathogenic Salmonella bacteria can be acquired by consuming of undercooked meat products and eggs. Antimicrobial resistance against antibiotics used in medicine is also a major concern. To help overcome these harmful effects on microbial food safety and human health, we are developing novel antimicrobial food-compatible formulations, one of which is described in the present study. METHODS: The composition of a bioprocessed (fermented) rice bran extract (BPRBE) from Lentinus edodes liquid mycelia culture was evaluated using gas chromatography and mass spectrometry, and the mechanism of its antibacterial effect against Salmonella Typhimurium, strain SL1344 was investigated in macrophage cells and in mice. RESULTS: BPRBE stimulated uptake of the bacteria into RAW 264.7 murine macrophage cells. Activation of the cells was confirmed by increases in NO production resulting from the elevation of inducible nitric oxide synthase (iNOS) mRNA, and in protein expression. Salmonella infection down-regulated the expression of the following protein biomarkers of autophagy (a catabolic process for stress adaptation of cellular components): Beclin-1, Atg5, Atg12, Atg16, LC3-I and LC3-II. BPRBE promoted the upregulation of protein expressions that induced bacterial destruction in autolysosomes of RAW 264.7 cells. ELISA analysis of interferon IFN-β showed that inflammatory cytokine secretion and bactericidal activity had similar profiles, suggesting that BPRBE enhances cell-autonomous and systemic bactericidal activities via autophagic capture of Salmonella. The treatment also elicited increased excretion of bacteria in feces and their decreased translocation to internal organs (cecum, mesenteric lymph node, spleen, and liver). CONCLUSIONS: The antibiotic mechanism of BPRBE involves the phagocytosis of extracellular bacteria, autophagic capture of intracellular bacteria, and prevention of translocation of bacteria across the intestinal epithelial cells. The new bioprocessing combination of mushroom mycelia and rice brans forms a potentially novel food formulation with in vivo antimicrobial properties that could serve as a functional antimicrobial food and medical antibiotic.